Material flow cost accounting (MFCA) – tool for the optimization of corporate production processes - Hyršlová, Jaroslava; Vágner, Miroslav; Palásek, Jiří (Business, Management and Economics Engineering, 2011)
The paper focuses on the Material Flow Cost Accounting method (hereinafter the “MFCA”). It presents an application of the MFCA within a manufacturing plant of the largest manufacturer of ceramic tiles in the Czech Republic – the company Lasselsberger. It shows the importance of data acquired from the MFCA system as well as their application for an optimization of manufacturing processes for specific conditions of a manufacturing plant of the company.